Prostate cancer progression and survival in BRCA2 mutation carriers - Tryggvadóttir, Laufey; Vidarsdóttir, Linda; Thorgeirsson, Tryggvi; Jonasson, Jon Gunnlaugur; Olafsdóttir, Elinborg Jona; Olafsdóttir, Gudridur Helga; Rafnar, Thorunn; Thorlacius, Steinunn; Jonsson, Eirikur; Eyfjord, Jorunn Erla; Tulinius, Hrafn (JNCI Journal of the National Cancer Institute, 2007)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: Mutations in the BRCA2 gene are associated with an increased risk of prostate cancer, but it is not known whether they are associated with progression of the disease. We compared prostate cancer-specific survival, disease stage, and tumor grade between prostate cancer patients carrying the Icelandic BRCA2 999del5 founder mutation and noncarriers. METHODS: Using population-based registries, we identified all 596 prostate cancer patients who were diagnosed in Iceland during 1955 through 2004 among 29603 male relatives of unselected breast cancer probands. BRCA2 mutation status could be determined for 527 patients (88.4%). Stage and grade were abstracted from original records, blindly with respect to mutation status, for a subgroup of 89 patients that included all mutation carriers and, for each carrier, two control patients without the BRCA2 999del5 mutation who were matched to the carrier on years of diagnosis and birth. Hazard ratios (HRs) and 95% confidence intervals (CIs) for prostate cancer-specific survival were estimated using multivariable regression models. All statistical tests were two-sided. RESULTS: The mutation was carried by 30 patients (5.7%). Compared with noncarriers, BRCA2 999del5 mutation carriers had a lower mean age at diagnosis (69.0 years versus 74.0 years; P = .002), more advanced tumor stage (stages 3 or 4, 79.3% versus 38.6%; P < .001), higher tumor grade (grades G3-4, 84.0% versus 52.7%, P = .007), and shorter median survival time (2.1 years, 95% CI = 1.4 to 3.6 years, versus 12.4 years, 95% CI = 9.9 to 19.7 years). Carrying the BRCA2 999del5 mutation was also associated with an increased risk of dying from prostate cancer (adjusting for year of diagnosis and birth, HR = 3.42, 95% CI = 2.12 to 5.51); the association remained after adjustment for stage and grade (HR = 2.35, 95% CI = 1.08 to 5.11). The prognosis of BRCA2 999del5 mutation carriers was not ...